Chemotherapy-based split stereotactic body radiation therapy for borderline resectable and locally advanced pancreatic cancer: study protocol of a prospective, single-arm phase II trial - Xiao-bo Li; Rong Zheng; Heguang Huang; Congfei Wang; Xiaoxue Huang; Qingliang Lin; Daxin Huang; Benhua Xu (BMJ Open)
Introduction The question of how to administer adequate chemotherapy to synchronise stereotactic body radiation therapy (SBRT) treatment strategy to maximise the benefits of neoadjuvant therapy for the improved prognosis of patients with borderline resectable (BRPC) and locally advanced (LAPC) pancreatic cancer is a challenging and debatable issue. No studies have yet evaluated the efficacy of split-course SBRT as the neoadjuvant chemoradiotherapy regimen. We aimed to study whether neoadjuvant chemotherapy plus split-course SBRT results in better outcomes in BRPC and LAPC patients.Methods and analysis Treatment-naïve patients with radiographically confirmed BRPC or LAPC, supporting biopsy results and no severe comorbidities will be enrolled. They will be treated with nab-paclitaxel plus gemcitabine (nab-P+Gem) chemotherapy plus split-course SBRT, followed by an investigator’s choice of continuation of treatment with nab-P+Gem or surgery. nab-P+Gem chemotherapy will commence on day 1 for each of six cycles: nab-paclitaxel 125 mg/m2 intravenous infusion over approximately 30–45 min, followed by gemcitabine 1000 mg/m2 intravenous infusion over about 30 min on days 1 and 15 of each 28-day cycle. During the first and second cycles of chemotherapy, SBRT will be given as a single irradiation of 10 Gy four times (days 2 and 16 of each 28-day cycle). The primary endpoint is progression-free survival; while the secondary outcomes are the time to treatment failure, disease control rate, overall response rate, overall survival, R0 resection rate and incidence of adverse effects.Ethics and dissemination The study protocol was approved by the Ethics Committee of Xiehe Affiliated Hospital of Fujian Medical University (No. 2019YF015-01). Results from our study will be disseminated in international peer-reviewed journals. All study procedures were developed in order to assure data protection and confidentiality.Trial registration number NCT04289792.